Nineteenth-century women's writing in wales : nation, gender and identity - Aaron, Jane, 1951- (Gender studies in Wales., 2010)
Argues that the way in which people came to perceive and to represent themselves as Welsh was profoundly affected by the gender ideologies prevalent during the Romantic and Victorian periods. This title introduces readers to a hundred Welsh women authors at work during the years 1780-1900, some writing in Welsh and some in English.